Ameliorative effects of Aquilaria malaccensis leaves aqueous extract on reproductive toxicity induced by cyclophosphamide in male rats - Abdul Razak, Redzuan Nul Hakim; Ismail, Faridah; Md Isa, Muhammad Lokman; Abdul Wahab, Azantee Yazmie; Muhammad, Hussin; Ramli, Roszaman; Raja Ismail, Raja Arif Shah (Penerbit Universiti Sains Malaysia, 2019)
Background: Cyclophosphamide (CP) is a widely used anti-neoplastic and immunosuppressive agent that is associated with adverse side effects including reproductive toxicity. Aquilaria malaccensis (AM) is a traditional medicinal plant which was reported to exhibit high anti-oxidant and free radical scavenging properties. The present study was aimed to evaluate the protective effects of AM leaves extract on sperm quality following toxic exposure to CP. Methods: Forty-eight male Sprague Dawley rats were allocated into eight groups of six rats (n = 6): control, CP only (200 mg kg−1 ), AM only (100 mg kg−1 , 300 mg kg−1 and 500 mg kg−1 ) and CP + AM (100 mg kg−1 , 300 mg kg−1 and 500 mg kg−1 ). Animals were sacrificed after 63 days of treatment and the sperm from the caudal epididymis was taken for sperm analysis. Results: The body and the reproductive organs weight, sperm count and motility did not differ between CP and other groups (P > 0.05). A significant increase (P < 0.05) in percentage of the dead and abnormal sperm were seen in the CP alone treated group compared to the control group. Co-administration of AM to the CP exposed rats significantly reduced the (P < 0.05) percentage of abnormal sperm as compared to the CP only group. Conclusion: Overall, the present results represent the potential of AM to protect against CP induced reproductive toxicity.